Radiación Ionizante a pacientes por haz primario durante Cineangiografía coronaria - Ramírez, Alfredo; Leyton, Fernando; Gamarra, Jorge; Oyarzún, Carlos; Silva, Ana María; Farías, Eric; Ugalde, Hector; Dussaillant, Gascón (Revista Hospital Clínico Universidad de Chile, 2001)
Resumen no disponible